Application of Group Counselling With the Cognitive Reappraisal Technique to Enhance Empathy Among Students - Siti Nurhaliza Muda; Yenti Arsini (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
Empathy is an essential skill in building healthy social relationships; however, in early adolescence, this ability is still developing and requires environmental support. This study aims to enhance students’ empathy through group counselling using the cognitive reappraisal technique at MTs IS Roudhotul Qurro. The research employed a qualitative case study approach involving eight Year VII students who demonstrated tendencies of low empathy in social interactions. Data were collected through observation, interviews, and documentation, and analysed using the Miles and Huberman model. The intervention was implemented over five progressive sessions, ranging from trust-building to the application of reappraisal in social simulations. The findings revealed a gradual increase in empathy, both during sessions and in daily life, including greater social engagement, communication initiative, and concern for peers. Follow-up monitoring also confirmed positive behavioural changes among the students. These findings demonstrate that the cognitive reappraisal technique is effective in enhancing students’ empathy both cognitively and affectively.